The inhibition of UDP-glucuronosyltransferases (UGTs) by tetraiodothyronine (T4) and triiodothyronine (T3). (4th March 2018) - Chen, Da-Wei; Du, Zuo; Zhang, Chun-Ze; Zhang, Wei-Hua; Cao, Yun-Feng; Sun, Hong-Zhi; Zhu, Zhi-Tu; Yang, Kun; Liu, Yong-Zhe; Zhao, Ze-Wei; Fu, Zhi-Wei; Gu, Wen-Qing; et al.
Abstract: 1. UDP-glucuronosyltransferases (UGTs) are important drug-metabolizing enzymes (DMEs) catalyzing the glucuronidation elimination of various xenobiotics and endogenous substances. Endogenous substances are important regulators for the activity of various UGT isoforms. Triiodothyronine (T3) and thyroxine (T4) are important thyroid hormones essential for normal cellular differentiation and growth. The present study aims to elucidate the inhibition behavior of T3 and T4 on the activity of UGT isoforms. 2. In vitro recombinant UGTs-catalyzed glucuronidation of 4-methylumbelliferone (4-MU) was used to screen the inhibition potential of T3 and T4 on the activity of various UGT isoforms. Initial screening results showed that T4 exerted stronger inhibition potential than T3 on the activity of various UGT isoforms at 100 μM. Inhibition kinetics was determined for the inhibition of T4 on the representative UGT isoforms, including UGT1A1, -1A3, -1A7, -1A8, -1A10 and -2B7. The results showed that T4 competitively inhibited the activity of UGT1A1, -1A3, -1A7, 1A10 and -2B7, and noncompetitively inhibited the activity of UGT1A8. The inhibition kinetic parameters were calculated to be 1.5, 2.4, 11, 9.6, 4.8 and 3.0 μM for UGT1A1, -1A3, -1A7, -1A8, -1A10 and -2B7, respectively. In silico docking method was employed to demonstrate why T4 exerted stronger inhibition than T3 towards UGT1A1. Stronger hydrogen bonds and hydrophobic interaction between T4 and activity cavity of UGT1A1 than T3 contributed to stronger inhibition of T4 towards UGT1A1. 3. In conclusion, more clinical monitoring should be given for the patients with the elevation of T4 level due to stronger inhibition of UGT isoforms-catalyzed metabolism of drugs or endogenous substances by T4.